THE EFFECTIVENESS OF EXPRESSIVE WRITING AND SOCIAL MEDIA AS EMOTIONAL RELEASE - Budiyono, Nararya Rahadyan; Sudiro, Suryo; Wibowo, Adityo Permana (Universitas Teknologi Yogyakarta, 2020)
Everyone has problem to solve. Each problem has positive and negative impacts but it makes someone stronger. This research aims to figure out the effectiveness of expressive writing and social media as media to express thought, ideas, and emotion of the users. The arrangement of research is descriptive studies through the examination a number of social media accounts by employing purposive sampling method. Expressive writing is an activity to direct to communication skill through writing for sharing feelings, thoughts, and anything that is wanted by the user without a feeling of being blamed by somebody else. Expressive writing becomes one of curative alternatives to solve traumatic experience and other psychological matters. Expressive writing helps someone to release emotional expression. Expressive writing in the era of technology is not only performed in conventional ways, handwriting but also performed through modern devices. Social media such as facebook, twitter, and path is a product of technology that is popularly used to share problems (expressive writing). This is phenomenology research. It shows that 150 user accounts of facebook, twitter, and path conduct expressive writing to release their emotional expression on problems that they are facing. Based on the research, it is found the impact of social anxiety on the reliance on social media that is significant and positive.